2015
DOI: 10.15740/has/au/10.4/307-311
|View full text |Cite
|
Sign up to set email alerts
|

Constraints faced by the respondents in adoption of sugarcane production technologies

Abstract: The present study was conducted with specific objectives to study knowledge and adoption of sugarcane production technology. For this study Latur district was selected and from Latur district two talukas viz., Chakur and Udgir were selected. From these two talukas twelve villages were selected randomly and ten respondents from each village were selected, i.e. 120 respondents from 12 villages constituted the sample for the study. Ex-Post Facto research design was used for the research study. The major constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Their knowledge and familiarity with sugarcane farming contribute to their ability to make informed decisions and address challenges efficiently. These findings are supported by Khandre et al (2020) [7] . www.extensionjournal.com Socio-economic and communication characteristics of sugarcane growers: Cosmopoliteness Table 2 indicated that, nearly two-fifth (37.50%) of sugarcane growers had medium cosmopoliteness followed by 32.50 percent , 30.00 percent had high and low market cosmopoliteness, respectively.…”
Section: Farming Experiencesupporting
confidence: 79%
“…Their knowledge and familiarity with sugarcane farming contribute to their ability to make informed decisions and address challenges efficiently. These findings are supported by Khandre et al (2020) [7] . www.extensionjournal.com Socio-economic and communication characteristics of sugarcane growers: Cosmopoliteness Table 2 indicated that, nearly two-fifth (37.50%) of sugarcane growers had medium cosmopoliteness followed by 32.50 percent , 30.00 percent had high and low market cosmopoliteness, respectively.…”
Section: Farming Experiencesupporting
confidence: 79%
“…The yield of sugarcane produced across India was approximately 83 thousand kilograms per hectare that year [8][9][10]. Sugarcane is an important cash or profit crop in the country [11,12]. Production technology for increasing the level of adoption, farmers need to be convinced about recent knowledge regarding production technologies.…”
Section: "Sustainablementioning
confidence: 99%